Improving the Breadth of the Host’s Immune Response to Lassa Virus - Zapata, Juan; Medina-Moreno, Sandra; Guzmán-Cardozo, Camila; Salvato, Maria (Pathogens (Basel), 2018)
In 2017, the global Coalition for Epidemic Preparedness (CEPI) declared Lassa virus disease to be one of the world’s foremost biothreats. In January 2018, World Health Organization experts met to address the Lassa biothreat. It was commonly recognized that the diversity of Lassa virus (LASV) isolated from West African patient samples was far greater than that of the Ebola isolates from the West African epidemic of 2013–2016. Thus, vaccines produced against Lassa virus disease face the added challenge that they must be broadly-protective against a wide variety of LASV. In this review, we discuss what is known about the immune response to Lassa infection. We also discuss the approaches used to make broadly-protective influenza vaccines and how they could be applied to developing broad vaccine coverage against LASV disease. Recent advances in AIDS research are also potentially applicable to the design of broadly-protective medical countermeasures against LASV disease.